ANNUAL PRODUCTION OF EROSION SEDIMENTS AND POSSIBILITY OF REDUCING IT IN THE AREA OF THE BRKA RIVER BASIN - Kaloper, Selman Edi; Čadro, Sabrija (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
In the conditions of climate change that are present in the territory of Bosnia and Herzegovina, extreme precipitation usually with high intensity is present, which resulted in soil degradation, erosion, landslides and even floods. Major floods in Bosnia and Herzegovina occurred in 2004, 2006, 2009, 2010, 2014, 2020 and 2021, with largest one in 2014. Currently, the most venerable municipalities to climate change are in the north of BiH, while the sensitivity is gradually declining towards the central, southern and eastern parts of the country.The aim of this study is to estimate the average annual production of erosion sediment (Wgod) and the total annual amount of transported sediment (Ggod) in the Brka River Basin in Bosnia and Herzegovina, using Gavrilovic's method supported by GIS techniques. Based on the projected current situation and soil intensity, an analysis of the possibility to reduce Wgod and Ggod with application of certain soil conservation measures.The average annual production of sediment in the Brka River Basin is 6,021.95 m³. Observed by sub-basins, the average annual sediment production (Wgod) ranged between 704 m³ in the Rahićka river sub-basin and 1,762 m³ in the Zovičica basin. The total annual sediment yield is highest in the Zovicica river basin (815.09 m3), and the total from the entire Brka river basin is 3,002.16 m³/year. In the case of replacing arable land with a combination of fruit and field production, the production of erosion sediments would decrease by 12.23%.